Hudud by the Taliban in Afghanistan and the relevance of Muhammad Syahrur's thought - Savitri, Desthia Irsa; Sobhan, Sobhan; Sulfinadia, Hamda (Priviet Social Sciences Journal, 2026)
This study is motivated by the continuing debate over the hudud in the modern era and its practical implications. It examines how the Taliban have applied hudud punishments in Afghanistan and assesses the relevance of Muhammad Syahrur’s contemporary legal thought on hudud punishments. Using a qualitative library-research approach, data were collected from books, scholarly literature, and relevant reports and then analyzed using content analysis and inductive reasoning. The findings indicate that during the Taliban's rule, the implementation of hudud tends to be harsher, more rigid, and more repressive, often raising concerns regarding due process and human rights. Both the Taliban's approach and Syahrur's discussion derive from the Qur'an and Hadith; however, Syahrur's theory of limits (nazariyyat al-hudud) frames divine law as having minimum and maximum boundaries, allowing space for contextual ijtihad that weighs public benefit (maslahah) in line with changing social realities while remaining within God's limits (sunnatullah).